Educational use of 3D models and photogrammetry content: The Europeana space project for Cypriot UNESCO monuments - Ioannides, Marinos; Chatzigrigoriou, Pavlos; Bokolas, Vassilis; Nikolakopoulou, Vasiliki; Athanasiou, Vasilis (My University, 2016)
Digital heritage data are now more accessible through crowdsourcing platforms, social media and blogs. At the same time, evolving technology on 3D modelling, laser scanning and 3D reconstruction is constantly upgrading and multiplying the information that we can use from heritage digitalisation. The question of reusing the information in different aspects rises. Educators and students are potential users of the digital content; developing for them an adaptable environment for applications and services is our challenge. One of the main objective of the EU Europeana Space project is the development of a holistic approach for educating people (grown ups and kids) on Monuments that are listed at UNESCO world heritage list, in Cyprus. The challenge was the use of Europeana Data (Pictures and the 3D objects) in a way that the information on the platform would be comprehensible by the users. Most of the data have little metadata information and they lack history and cultural value description (semantics). The proposed model ction is based on the cross cultural approach which responds to the multicultural features of present era but at the same time to the contemporary pedagogical and methodological directions. The system uses all innovative digital heritage resources, in order to help the user, in a UX friendly way, to learn about the different phases of the monument, the history, the pathology state, the architectural value and the conservation stage. The result is a responsive platform, accessible through smart devices and desktop computers, (in the frame of "Bring Your Own Device" a.k.a. BYOD) where every Monument is a different course and every course is addressed to different age groups (from elementary level to adults' vocational training).
Keywords: 3D models; Cross-cultural; Digital heritage; Education